FORMULATION DEVELOPMENT AND EVALUATION OF NOVEL FIXED DOSE COMBINATION OF S (-) PANTOPRAZOLE AND MOSAPRIDE CITRATE BY TABLET IN CAPSULE APPROACH - PIMPLE, SRIKANT; MAURYA, PRAVIN; JOSHI, AKASH; SALUNKE, MOHAN; SINGH, RUBY (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The main objective of the present study was to formulate a fixed dose combination of chirally pure S (-) Pantoprazole and Mosapride citrate tablets. Since no systematic studies on design and development of S (-) Pantoprazole and Mosapride citrate tablets in capsule approach are available in literature, we propose to develop a suitable formulation to characterize in-vitro release profile of both the tablets in capsules. Chirally pure S (-) Pantoprazole tablets were prepared as delayed release and Mosapride citrate tablets were prepared as immediate release tablets. Methods: Enteric coating was done on S (-) Pantoprazole tablets to modify its release in 6.8 phosphate buffer. In-vitro dissolution of capsule containing both the tablets was performed in two different media, 0.1N HCl and 6.8 phosphate buffer respectively. All Physico-chemical parameters for both the tablets as well as capsules were evaluated individually and were found well within the specified limits. Result: Initially dissolution was performed in 0.1 N HCl in which immediate release tablet of Mosapride dissolve completely and pantoprazole tablets remains as it is due to enteric coating. Further tablet was placed in 6.8 phosphate buffer in which delayed release tablets of S (-) Pantoprazole gives complete release. Drug product was found stable during accelerated stability studies for 6 month at 40Â°C/75% RH. Conclusion: A stable and robust formulation of S (-) Pantoprazole and Mosapride citrate as fixed dose combination was developed and evaluated. Tablet in capsule approach was developed and results were well within the specified limits. Keywords: S (-) pantoprazole, Mosapride citrate, Modified release, Fixed-dose combination, Delayed release.